The use of computer image analyses in the assessment of chosen histoclinical features of nephroblastoma cells in children - Kobos, Józef; Dembski, Piotr; Taran, Katarzyna (Polish Journal of Pathology, 2011)
The goal of the research was to assess the nuclear morphometric discriminant function (MVf) in the analyzed group of nephroblastomas and to evaluate its potential prognostic value. We found a statistically important correlation between the favourable histology of Wilms’ tumours (according to SIOP 93-01 and SIOP 2001 classifications of kidney tumours of childhood) and low values of MVf discriminant function, which was also associated with the best prognosis for the patients. We believe that MVf assessment may be a helpful tool in making prognosis in doubtful cases of nephroblastomas in children.